Englishes in the cityscape of Muscat. Issue 2 (3rd June 2020) - Tuzlukova, Victoria; Mehta, Sandhya Rao
Abstract: This paper examines the linguistic landscape in Muscat with specific reference to its public spaces as reflected in street signs and commercial signage. Based on the multilingual theories of Landry and Bourhis (1997) and Cenoz and Gorter (2006), it explores the various ways in which English is localized, re‐shaped, and recreated to fit into the multi‐ethnic social fabric of the city. As much research suggests, the more Arabized version of English has become increasingly popular in the cosmopolitan structure of the city, providing space for a language which is at once structurally imaginative and colloquially accessible. This aptly reflects a city that is commercially ambitious, has an international resident population, and is aspiring to be a tourist hub.